AB0040 Effects of CC-220, A CRL4 Cereblon E3 Ubiquitin Ligase Modulator, on Immune Responses. (9th June 2015) - Ye, Y.; Schafer, P.; Thomas, M.; Weiss, D.; Gaudy, A.; Yang, Z.; Liu, L.; O'Mara, E.; Palmisano, M.
Abstract : Background: Cereblon (CRBN) is a component of the E3 ubiquitin ligase complex, including cullin 4A, DNA damage binding protein 1, and regulator of cullin 1. CC-220 binds to cereblon, affecting the ubiquitin E3 ligase activity and mediating antiproliferative and immunomodulatory effects on lymphocytes. CC-220 is an orally available immunomodulator under development for autoimmune diseases. Objectives: Assess the effects of CC-220 on immune responses to tetanus toxoid (T-cell-dependent antigen) and pneumococcal polysaccharide (T-cell-independent antigen), peripheral T and B lymphocytes, ex vivo cytokine productions, and in vitro rheumatoid factor antibody production from healthy subject samples. Methods: Effects of CC-220 on immune responses were assessed as part of a multiple-ascending dose study in healthy subjects. Protective levels of antitetanus titer were required for enrollment. Six subjects received CC-220 1 mg QD and 3 subjects received placebo QD for 28 days. On Day 14, subjects received vaccines of 23-valent pneumococcal polysaccharide (PPV23) and tetanus toxoid. Antibody responses, peripheral B- and T-cell counts, and ex vivo cytokines were measured. In addition, the effect of CC-220 on autoantibody production in vitro was assessed using activated and differentiated human peripheral blood mononuclear cells from donors with rheumatoid arthritis. Results: CC-220 reduced immune responses to PPV23, with 60% of CC-220-treated subjects (3/5) showing normal response (≥2-fold of baseline or >1 μg/mL increase from baseline in antibodies against >70% serotypes) compared with 100% of placebo subjects (2/2) showing normal responses. However, the reduction was mild, as all CC-220 subjects were able to mount normal immune responses to 12 out of 23 serotypes. Immune responses to tetanus toxoid were similar between CC-220-treated subjects and placebo subjects, with 60% of CC-220 subjects (3/5) and 50% of placebo subjects (1/2) demonstrating a 4-fold increase from baseline in antitetanus IgG titer. Following 14 days of CC-220 dosing, peripheral B-cell counts were decreased from baseline by 79%, and T-cell counts were decreased by 22%. In ex vivo assays, CC-220 increased IL-2 and interferon-γ production from anti-CD3-stimulated whole blood and inhibited IL-1α and IL-1β production from lipopolysaccharide-stimulated whole blood. In an in vitro assay using cells from donors with rheumatoid arthritis, CC-220 inhibited the production of rheumatoid factor. Conclusions: CC-220 1 mg QD modestly decreased the T-cell-independent antibody response to PPV23, but did not affect the recall response to tetanus toxoid, a T-cell-dependent antibody response. These responses are consistent with CC-220 inhibition of B-cell differentiation while enhancing T-cell cytokine production. Disclosure of Interest: Y. Ye Employee of: Celgene Corporation, P. Schafer Employee of: Celgene Corporation, M. Thomas Employee of: Celgene Corporation, D. Weiss Employee of: Celgene Corporation, A. Gaudy Employee of: Celgene Corporation, Z. Yang Employee of: Celgene Corporation, L. Liu Employee of: Celgene Corporation, E. O'Mara Employee of: Celgene Corporation, M. Palmisano Employee of: Celgene Corporation